Model Komunikasi “Virginia Satir” di Keluarga Konsensual Dalam Membentuk Ketahanan Keluarga Selama Pandemi COVID-19 - andi setyawan (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Communication is basically an important thing to maintain family harmony. The ability of family members to survive will depend on their ability to communicate. Virginia Satir describes good communication as communication that is open, clear, honest and congruent. The I-Message concept from Virginia Satir is believed to be able to build congruent interpersonal communication (within the family). The application of this communication is very appropriate to be applied to the type of consensual family, namely a family that has high conformity and conversation. Good application of IMessage in consensual families will lead to solid family resilience, namely families that are resistant to external threats. In early 2020, Indonesia experienced a national disaster with the COVID-19 pandemic. Data from the DKI Jakarta Health Office in February 2021 stated that the largest contributor to Covid-19 was the family cluster. In this condition the resilience of the family is tested. Therefore, this study wanted to see Virginia Satir's communication model in a consensual family in forming family resilience from the threat of Covid-19. The method used in this research is a case study with a qualitative approach. The communication paradigm used is postpositivist with a sociopsychological tradition. The informants in this study were a consensual family domiciled in the Petukangan Selatan village-South Jakarta. Test the validity of the data using source triangulation. The results showed that the application of 5 I-Message formulas consisting of: Sensing, Emotion, Want, Behavior, and Effect in consensual family communication led to more intensive interaction and communication. Families have become more solid in the face of the Covid-19 pandemic so that family resilience is formed strongly.